English English - Rifdah Hanifah; Nabila Aulia Tsaqifah; Deannisa Fajriaty (Universitas Airlangga, 2026)
Background: Through metabolic, immunological, and neurodevelopmental pathways, maternal microbiome is critical for fetal growth and perinatal health through metabolic, immunological, and neurodevelopmental pathways. Pregnancy-related nutritional therapies have emerged as potential strategies for improving maternal and newborn health by influencing the mother's microbiota. The goal of this review is to compile the available data on nutritional therapies that target the microbiota during pregnancy and their effects on postnatal outcomes. Objectives: To synthesize the current evidence on microbiome-targeted nutritional interventions during pregnancy and their effects on perinatal outcomes. Methods: A systematic literature search was conducted using PubMed to identify relevant studies published between 2020 and 2026. The search employed keywords related to pregnancy, maternal nutrition, the microbiome, and perinatal outcomes. Original studies investigating dietary or nutritional interventions during pregnancy and their effects on maternal microbiota and microbiome-related or perinatal outcomes were included in this review. Eligible studies underwent title and abstract screenings, followed by full-text assessments. Due to methodological variability across studies, the findings were synthesized using a narrative approach. Results: The results indicate that the composition and function of the maternal microbiota can be changed by interventions such as probiotics, prebiotics, specific dietary patterns (such as the Mediterranean diet), and balanced energy and protein supplements. These interventions may affect the colonization of the newborn microbiota, immunological development, metabolic programming, and infection risk through mechanisms involving microbial metabolites, including short-chain fatty acids and breast milk-mediated pathways. However, due to differences in study design, microbiome assessment methods, intervention categories, and outcome measurements, the evidence remains inconsistent. Conclusion: Nutritional interventions targeting the microbiome during pregnancy have the potential to improve perinatal outcomes. However, substantial methodological heterogeneity among studies and limited longitudinal evidence restrict their translation into standardized clinical recommendations. Further rigorously designed studies with standardized methodologies and long-term follow-ups are needed to clarify their efficacy, mechanisms, and clinical relevance.